Preparação e caracterização de nanopartículas magnéticas multifuncionais para imageamento e liberação controlada de fármacos - Ana Paula de Figueiredo Monteiro (2014)
Magnetic nanoparticles are being extensively studied for biomedical applications due to their multifunctional character. Nanoparticles of iron oxide, for example, can act not only as a contrast agent in MRI but also as magnetically guided vehicle, taking the drug to a specific part of the body. On the other hand, cyclodextrins play major roles in many fields such as drug delivery system through the inclusion compounds formation. In the present work, iron oxide nanoparticles functionalized with -cyclodextrin (betaCD) and2-hydroxy-propyl--cyclodextrin (HPbetaCD) were obtained by coprecipitation method and coated with the anion citrate. In this case, the system was tested to deliver the drug approved for use in humans, irinotecan (IRI), which is an intravenous antineoplasic agent, but still with many side effects. Thus, were prepared four different devices: ferrite-betaCD-IRI ferrite-HPbetaCD-IRI, ferrite-betaCD-citrate-IRI and ferrite-HPbetaCD-citrate-IRI. In this context, one can understand the ferrites as iron oxides with the formula Fe3O4, although the ferrite term includes iron oxides with other divalent metals. The nanoparticles were characterized by FTIR, measurements of particles size and Zeta potential based on dynamic light scattering principle technique, X-ray diffraction, transmission electron microscopy, thermogravimetric analysis, elemental analysis of CHN, measurements of magnetization, Mössbauer and atomic absorption spectroscopy. The in vitro irinotecan release profile and its cytotoxicity biological assays, in cancer cells, were assessed by the MTT method. The results showed that the nanoparticles have a spherical morphology, with diameters varying between 8-10 nm, with superparamagnetic behavior at room temperature. The citrate coating proved important against the oxidations and for a reduced aggregation of the nanoparticles, also assuring a higher interaction with the drug and slightly slower release kinetics. The ferrites functionalization with betaCD has proven better than with HPbetaCD, with a mass percentage of these two compounds of 6% and 3%, respectively. The MTT assay showed that all devices have a concentration-dependent cytotoxicity toward the A431 linage of cancer cells, with IC50 near of the pure drug.